Le personal branding des écrivains sur les réseaux sociaux : gestion de l’identité et de la notoriété en ligne - Louis Wiart (Communiquer)
Based on a questionnaire survey supported by interviews, this article examines the characteristics of writers’ engagement on social networks and its effects on the online reputation. Our results show that social networks are first used for communication and promotional purposes by writers, who develop forms of digital identity management and self-marketing. Their motivations oscillate between the pleasure and the taste they feel for this online sharing activity and the positive consequences they can bring in terms of visibility and reputation. Also, we seek to identify the explanatory factors of writers’ online reputation. While several factors play a significant role (type of writing, intensity and nature of digital practices), success on social networks is primarily superimposed with editorial success, the online audiences tending to focus around the most established authors in the publishing world.